2021
DOI: 10.3390/ijerph18084335
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Airborne Virus Threats in the Food Industry: A Proactive Approach

Abstract: The current SARS-COVID-19 crisis has demonstrated the dangers that airborne virus (AV) pandemics pose to the health of all workers (particularly in the meat processing industry), the economic health of the food industry, and food security. The impact that the current pandemic has had on the food industry points to the need for a proactive rather than reactive approach towards preventing future AV outbreaks. Such a proactive approach should be based on empirical assessments of current AV food safety practices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The effect of selenium nanoparticles on different plant species can vary greatly depending on the stage of plant growth, the duration of exposure, and also the shape, size, chemical composition, concentration, surface structure, aggregation and solubility of the nanoparticle [29,30]. Earlier studies have shown that selenium nanoparticles can enhance antioxidant potential [28], promote plant growth [16,31,32] and positively affect the quality and quantity of the resulting crop [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of selenium nanoparticles on different plant species can vary greatly depending on the stage of plant growth, the duration of exposure, and also the shape, size, chemical composition, concentration, surface structure, aggregation and solubility of the nanoparticle [29,30]. Earlier studies have shown that selenium nanoparticles can enhance antioxidant potential [28], promote plant growth [16,31,32] and positively affect the quality and quantity of the resulting crop [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The result of the experiment was evaluated based on the analysis of the state of the gastrointestinal tract, liver, spleen, and kidneys during the pathoanatomical autopsy of laboratory mice. The biopreparation was considered non-toxic if all laboratory animals remained viable, and no pathoanatomical changes were recorded during their autopsy [28,29].…”
Section: Methodsmentioning
confidence: 99%
“…Sorbents based on the ion-exchange interaction of the ligand with LDL, such as Liposorber D® (Kaneka, Japan) and DALI® (Fresenius, Germany), had the lowest specificity for LDL, the most specific were the immunosorbent " LDL-300" ® (Russia) and " LDL-45" ® ("Tosoh", Japan). However, despite the high efficiency of existing sorbents for LDL apheresis, this procedure is not available to everyone who needs it [17,18]. This is primarily due to the high cost of sorbents.…”
Section: Introductionmentioning
confidence: 99%